Effect of Air‐Particle Abrasion Protocol and Primer on The Topography and Bond Strength of a High‐Translucent Zirconia Ceramic. Issue 3 (12th May 2021) - Khanlar, Leila Nasiry; Takagaki, Tomohiro; Abdou, Ahmed; Inokoshi, Masanao; Ikeda, Masaomi; Takahashi, Akifumi; Yoshihara, Kumiko; Nagaoka, Noriyuki; Nikaido, Toru; Blatz, Markus B.; Tagami, Junji
Abstract: Purpose: To evaluate effect of air‐particle abrasion protocol and primer on surface topography and bond strength of resin cement to high‐translucent zirconia ceramics. Materials and Methods: Two hundred disk‐shaped high‐translucent zirconia specimens of 5Y‐PSZ were prepared. The specimens were assigned to 5 groups in terms of particle type and air‐particle abrasion pressure: (1) control, (2) alumina with 0.2 MPa‐air pressure [AB‐0.2], (3) alumina with 0.4 MPa‐air pressure [AB‐0.4], (4) glass beads with 0.2 MPa‐air pressure [GB‐0.2], and (5) glass beads with 0.4 MPa‐air pressure [GB‐0.4]. Two different primers 1% MDP (Experimental) and MDP‐silane primer (Clearfil Ceramic Primer Plus) was also tested. Stainless steel rods were bonded to the 5Y‐PSZ specimens with PANAVIA V5. For each group, the tensile bond strength (TBS) was measured after 24‐hour water storage (n = 10) and after 5000 thermal‐cycling (n = 10) at crosshead speed of 2 mm/min. The data were statistically analyzed using Weibull analysis. Surface roughness (Sa) was measured using a 3D‐Laser Scanning Confocal Microscope (n = 5) and analyzed by t‐test with Bonferroni correction. Surface topography using scanning electron microscopy (SEM) and surface elemental analysis using energy dispersion spectroscopy (EDX), and cross‐section SEM at the interface with composite cement were also investigated. Results: In MDP‐silane groups, the highest TBS was observed in AB‐0.4 after 24 hours and GB‐0.4 after thermal‐cycling ( p < 0.05). In MDP groups, AB groups resulted in the significantly higher TBS than GB groups ( p < 0.05). AB‐0.4 group showed the highest Sa value compared to all groups ( p < 0.005), meanwhile GB groups did not show different Sa compared to control ( p > 0.005). Conclusion: Air‐abrasion with different particle and blasting pressure can improve bonding to zirconia with proper primer selection. Particularly, glass beads abrasion followed by MDP‐silane primer and alumina abrasion followed by MDP primer alone provided stable bond strength of resin cement to high‐translucent zirconia after aging. High‐translucent zirconia abraded with glass beads achieves a desirable bonding performance without creating surface microcracks which may hinder zirconia's mechanical properties.